ENHANCING COST ACCURACY AND PRICING DECISIONS THROUGH ACTIVITY-BASED COSTING: EVIDENCE FROM A SMOKED SKIPJACK TUNA PROCESSING ENTERPRISE IN INDONESIA - Tessa Cantika Dwi Prasetyo; Anisa Restuti; Triska Wahyuningtyas (Universitas Tulungagung, 2024)
Accurate production cost estimation is essential for supporting pricing decisions and maintaining business competitiveness, particularly in small-scale fisheries processing enterprises. However, many micro and small enterprises continue to rely on conventional costing methods that inadequately allocate manufacturing overhead, resulting in less reliable cost information for managerial decision-making. This study addresses this gap by evaluating the application of Activity-Based Costing (ABC) to improve the accuracy of production cost calculation in a smoked skipjack tuna processing enterprise. The objective of this study was to assess the effectiveness of the ABC method in determining the cost of production and its implications for pricing decisions. A quantitative descriptive research design was employed using primary data collected from Ikan Tongkol Asap Bu Tutik, a smoked skipjack tuna processing enterprise located in Karangtalun Village, Tulungagung Regency, Indonesia. Data were obtained through direct observation, in-depth interviews, and discussions with the business owner. The data were analyzed using the Activity-Based Costing approach by identifying production activities, determining cost drivers, establishing activity cost pools, and allocating manufacturing overhead based on actual resource consumption. The findings indicate that the total production cost was Rp580,000 for 60 bundles of smoked skipjack tuna, resulting in a production cost of Rp9,667 per bundle. With a selling price of Rp15,000 per bundle, the enterprise achieved a gross profit of Rp5,333 per bundle and a profit margin of 35.55%. The findings demonstrate that Activity-Based Costing provides more accurate and transparent cost information, thereby supporting better pricing decisions, improving cost management, and enhancing managerial decision-making in fisheries-based micro and small enterprises.